(untitled) (Papeles, 2026)
Introduction: This article examines the transformation of nutrition professionals into educators through reflection-in-action, taking as a case the Prevention Project (2019-2023). It seeks to understand how situated pedagogical practices support the construction of a teaching identity among professionals traditionally trained from a technical perspective. Methodology: A qualitative study was conducted using narrative analysis of interviews with educators-in-training who participated in educational sessions with schoolchildren and families. The corpus was organized into emerging categories related to didactic methodologies, reflexivity, construction of the teaching role, and tensions between technical discourse and lived experience. Results and discussion: The narratives show that pedagogical practice operated as a reflective learning space in which educators moved from a technical performance toward a critical understanding of their role. Reflection-in-action enabled them to adjust strategies, question decisions, and value error as a formative opportunity. Cooking, play, multisensory experiences, and participatory dynamics emerged as central mediations for generating meaningful learning and strengthening educational relationships. Tensions also surfaced between theory and practice, instrumental versus pedagogical uses of didactic resources, and the need to integrate technical knowledge and experience in a dialogical and situated manner. Conclusions: When lived as a reflective experience, pedagogical practice reshapes the identity of nutritionists and guides them toward an ethical, sensitive, and socially committed educational role aligned with the right to food. Strengthening training processes that integrate systematic reflection, teaching accompaniment, and real educational settings is recommended, recognizing teaching as a transformative praxis in non-pedagogical fields.